Kebijakan Penanggulangan HIV/Aids dalam Perspektif Health Policy Triangle Analysis di Kota Surabaya - Hanifah, Lailatul; Kriswibowo, Arimurti (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Surabaya City is the highest case of HIV/AIDS cases in East Java. This is a special concern for the Surabaya City government to handle this health case so that it does not spread more widely.. This study aims to describe and explain HIV/AIDS Prevention Policy in the Perspective of the Health Policy Triangle Analysis in the City of Surabaya.The type of research used in this research is descriptive qualitative. The research was conducted at the Surabaya city health office, community health centers and NGOs concerned with HIV/AIDS in the city of Surabaya. The results showed that (1) the actors involved in this treatment, care and support effort were the Surabaya City Health Office, UPTD Community Health Centers, Hospitals, Case Managers (MK), PLWHA, and NGOs. (2) the contents of the HIV/AIDS prevention policies in the city of Surabaya that have been implemented include ARV Treatment, Opportunistic Infection Monitoring (OI), Viraload Testing, Home Care, Supplementary Feeding (PMT), and Care Givers. (3) the context of the HIV/AIDS prevention policy in the city of Surabaya is a solution to an increase in the number of HIV/AIDS as well as guidelines for the prevention of HIV/AIDS in the city of Surabaya, although there are still problems namely the community's stigma against PLHIV which causes non-compliance of PLHIV in carrying out treatment in PDP services. (4) the process of implementing HIV/AIDS prevention policies in the city of Surabaya has been running well in accordance with the provisions of the regulations. The Surabaya city government has provided 43 PDP services as a referral for ODHA in carrying out treatment and care.